2012
DOI: 10.1177/2158244012465763
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Testing of the Codependency-Overeating Model in Undergraduate Social Science Students in a Mississippi College

Abstract: Overeating is a common eating disorder and often leads to obesity and to significant physical, emotional, and social problems often warranting nursing care. Codependency has expanded beyond the chemical dependency field and describes the dysfunctional pattern of behavior of an individual in a relationship with another person or from survival in a dysfunctional family of origin. The psychological and behavioral factors surrounding overeating are noted frequently in the literature but are not emphasized in most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
1
4
0
1
Order By: Relevance
“…Also, the most common selfreported psychological problem was depression/mood disorders; this is supported by data from the literature, which indicate that the most prevalent psychological disorders associated with codependency are anxiety, depression, anger, and compulsiveness (Bynum et al, 2012;Snow, 1997). In a study investigating codependency and related health variables, Martsolf, Sedlak, and Doheny (2000) reported that codependency and perceived health correlate to functional ability and depression, a finding which is consistent with our results.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Also, the most common selfreported psychological problem was depression/mood disorders; this is supported by data from the literature, which indicate that the most prevalent psychological disorders associated with codependency are anxiety, depression, anger, and compulsiveness (Bynum et al, 2012;Snow, 1997). In a study investigating codependency and related health variables, Martsolf, Sedlak, and Doheny (2000) reported that codependency and perceived health correlate to functional ability and depression, a finding which is consistent with our results.…”
Section: Discussionsupporting
confidence: 56%
“…Higher scores indicate higher levels of codependency (Ancel, 2012;Hughes-Hammer et al, 1998). Also, the scores of the scale are graded as follows: low-minimal codependency (25-50), mild codependency (51-75), moderate codependency (76-100), and severe codependency (101-125;Bynum, Boss, Schoenhofer, & Martsolf, 2012;Martsolf et al, 1999).…”
Section: Codependency Assessment Tool (Codat)mentioning
confidence: 99%
“…Our literature search yielded two relevant journal articles (Fowler & Risner, 1994; Olson, 2001), eight doctoral dissertations (Bynum, 2012; Casalenuova, 2002; Lamb, 1998; Manister, 2012; Ngangana, 2014; Roojanavech, 2012; Simpson, 2001; Talato, 2015), and one master’s thesis (Todd, 2011). Inasmuch as we regard health policy as a social issue within the context of the Neuman systems model, we added our journal article about conceptual models and health policies (Aronowitz & Fawcett, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Fowler and Risner (1994) and Olson (2001) apparently did not regard the social issues as client systems. Bynum (2012) did not identify what the social difficulties or problems are. Authors of other dissertations and the master’s thesis did not explicitly identify social issues.…”
Section: Examples Of Social Issuesmentioning
confidence: 99%
“…Ayrıca literatürde kök aile ile karşılıklı bağımlılığın ilişkili olduğunu belirten hemşirelik öğrencileri (22) ve sosyal bilimler (23) örnekleminde yapılan çalışmalara rastlansa da bu ilişkinin hemşire örnekleminde niteliğini ortaya koyacak daha fazla çalışmaya gereksinim duyulmaktadır.…”
Section: Sonuç Ve öNeri̇lerunclassified